2021
DOI: 10.1093/pubmed/fdab081
|View full text |Cite
|
Sign up to set email alerts
|

Will the demands by the covid-19 pandemic increase the intent to quit the profession of long-term care managers? A repeated cross-sectional study in Germany

Abstract: The Corona pandemic poses major demands for long-term care, which might have impacted the intention to quit the profession among managers of long-term care facilities. We used cross-sectional data of an online survey of long-term care managers from outpatient and inpatient nursing and palliative care facilities surveyed in April 2020 (survey cycle one; n = 532) and between December 2020 and January 2021 (survey cycle two; n = 301). The results show a significant association between the perceived pandemic-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
1
13
0
3
Order By: Relevance
“…One recent survey of nursing home managers (n ¼ 301) found that 1 in 5 considered quitting their profession often or very often during the pandemic. 42 This is consistent with career-ending dilemmas, which many of our participants revealed in why they considered leaving the sector. Leaders in our study were, on average, within 5-10 years of retirement.…”
Section: Discussionsupporting
confidence: 86%
“…One recent survey of nursing home managers (n ¼ 301) found that 1 in 5 considered quitting their profession often or very often during the pandemic. 42 This is consistent with career-ending dilemmas, which many of our participants revealed in why they considered leaving the sector. Leaders in our study were, on average, within 5-10 years of retirement.…”
Section: Discussionsupporting
confidence: 86%
“…The COVID-19 pandemic placed heavy pressure on healthcare systems, resulting in excessive job demands and tumultuous work environments. Increases in workload were widely found to be positively correlated with turnover intention among HCWs [ 38 , 45 , 55 , 56 ]. In addition, HCWs who worked long hours, or faced an increase in working hours due to the pandemic, were more prone to experiencing turnover intention [ 40 , 50 , 55 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Für die Zukunft äußerten die Interviewten Befürchtungen bezüglich des Personaleinsatzes, u. a. dass erfahrene Mitarbeiter*innen als Reaktion auf die Pandemiekrise den Pflegeberuf verlassen könnten, eine Befürchtung, die sich mittlerweile national und international bestätigt hat [ 8 , 18 ]. Gebraucht würden klarere Information und Anordnungen zur Umsetzung von Maßnahmen der Infektionsprävention und -kontrolle, z.…”
Section: Diskussionunclassified